Growth, photosynthetic function, and stomatal characteristics of Persian walnut explants in vitro under different light spectra - Saeedi, Seyyed Arash; Vahdati, Kourosh; Sarikhani, Saadat; Daylami, Shirin Dianati; Davarzani, Maryam; Gruda, Nazim S.; Aliniaeifard, Sasan (Frontiers in Plant Science, 2023)
Light plays a crucial role in photosynthesis, which is an essential process for plantlets produced during in vitro tissue culture practices and ex vitro acclimatization. LED lights are an appropriate technology for in vitro lighting but their effect on propagation and photosynthesis under in vitro condition is not well understood. This study aimed to investigate the impact of different light spectra on growth, photosynthetic functionality, and stomatal characteristics of micropropagated shoots of Persian walnut (cv. Chandler). Tissue-cultured walnut nodal shoots were grown under different light qualities including white, blue, red, far-red, green, combination of red and blue (70:30), combination of red and far-red (70:30), and fluorescent light as the control. Results showed that the best growth and vegetative characteristics of in vitro explants of Persian walnut were achieved under combination of red and blue light. The biggest size of stomata was detected under white and blue lights. Red light stimulated stomatal closure, while stomatal opening was induced under blue and white lights. Although the red and far-red light spectra resulted in the formation of elongated explants with more lateral shoots and anthocyanin content, they significantly reduced the photosynthetic functionality. Highest soluble carbohydrate content and maximum quantum yield of photosystem II were detected in explants grown under blue and white light spectra. In conclusion, growing walnut explants under combination of red and blue lights leads to better growth, photosynthesis functionality, and the emergence of functional stomata in in vitro explants of Persian walnuts.